КОНЦЕПТ ‘ДОМ’ В ХАНТЫЙСКОМ И НЕНЕЦКОМ ЯЗЫКОВОМ СОЗНАНИИ - Potpot, Rimma Mihajlovna (Sovremennye issledovaniya sotsialnykh problem, 2018)
Целью исследования является конструирование ассоциативного поля концепта ‘Дом’ в хантыйской и ненецкой концептосферах по результатам ассоциативного эксперимента и выявление общих и специфических когнитивных признаков данного концепта в указанных концептосферах. Ассоциативный эксперимент был проведен среди носителей хантыйского языка в г. Ханты-Мансийск, г. Белоярский, с. Казым Ханты-Мансийского автономного округа – Югры, среди носителей лесного диалекта ненецкого языка – в с. Казым, в д. Нумто Белоярского района и частично в с. Варъеган Нефтеюганского района ХМАО-Югры.Результаты. Сопоставительный анализ выявил близкое по структуре представление о доме двух народов, проживающих рядом. Важными для них являются характеристика дома, его составные части, убранство и родственные отношения. Дом для ненцев ассоциируется с чумом. В структуре концепта ‘Дом’ закреплены реакции сознания носителей на явления бытия. У хантов наибольшее количество реакций связано с характеристикой дома, с действиями, со структурой и пространством дома, религиозными представлениями, фольклорными образами и национальной принадлежностью дома.Область применения результатов. Результаты данного ассоциативного эксперимента могут быть применены в межъязыковых и межкультурных исследованиях, при составлении национальных портретов носителей хантыйского и ненецкого языков и при изучении взаимодействия языковых систем. In the article, the associative field of the concept ‘Dwelling place’ of the Khanty and Nenets spheres of conceptsis built following the results of the associative experiment, as well as general and specific cognitive features of the above-mentioned concept are revealed. The associative experiment was conducted among the Khanty native speakers in the cities of Khanty-Mansiysk, Beloyarsk, the village of Kazym (Khanty-Mansiysk Autonomous Okrug-Ugra), among the native speakers of the forest dialect of the Nenets language – in the village. Kazym, Numto of Beloyarsk region and partially in the village of Varjegan of Nefteyugansk district of the Khanty-Mansiysk Autonomous Okrug-Ugra.Results. The comparative analysis revealed that the representation of the concept ‘Dwelling place’ of the two peoples living side by side has a lot in common. It is the characteristics of the dwelling place, its components, decoration and family relations that are significant. The dwelling place for the Nenets is associated with the chum (rawhide tent). In the structure of the concept house pinned the reaction of the consciousness of the media phenomena of existence. For the Khanty, the greatest number of reactions are associated with the characteristics of the house, there are reactions associated with actions, with the structure and space of the dwelling place, religious beliefs, folklore images and national identity of the house.Practical implications. The results of the associative experiment can be applied in cross-language and cross-cultural studies, in the preparation of national portraits of the Khanty and Nenets languages native speakers as well as in the study of the interaction of language systems.